Predictors of Revision Surgical Procedure Excluding Wound Complications in Adult Spinal Deformity and Impact on Patient-Reported Outcomes and Satisfaction: A Two-Year Follow-up. (6th April 2016) - Passias, Peter G.; Soroceanu, Alexandra; Yang, Sun; Schwab, Frank; Ames, Christopher; Boniello, Anthony; Smith, Justin; Shaffrey, Christopher; Boachie-Adjei, Oheneba; Mundis, Gregory; Burton, Douglas; Klineberg, Eric; et al.
Abstract : Background: The surgical procedure to treat adult spinal deformity is challenging, with high rates of complications, including revision procedures performed to repair instrumentation failure or unplanned surgical complications. This study quantifies the incidence of, identifies predictors for, and determines health-related quality-of-life changes associated with revision procedures to treat adult spinal deformity. Methods: We analyzed a multicenter database of patients who underwent a surgical procedure for adult spinal deformity, which was defined as having an age of eighteen years or older and scoliosis of ≥20°, sagittal vertical axis of ≥5 cm, pelvic tilt of ≥25°, and/or thoracic kyphosis of >60°. We focused on demographic, radiographic, health-related quality-of-life, and operative data at the two-year follow-up. Patients with primary infections were excluded. Predictive and confounding variables for revisions were identified using univariate analysis and multivariate logistic regression modeling. Results: Two hundred and forty-three patients were included in this study; of these patients, forty (16.5%) underwent a revision surgical procedure (15% of these at six weeks, 38% between six weeks and one year, and 48% between one and two years). Screw or cage-related implant complications were the most common indications for revision, followed by proximal junctional kyphosis and rod failure. Positive predictors for a revision surgical procedure included total body mass, with an odds ratio of 1.33 (95% confidence interval, 1.04 to 1.70) per 10-kg increase, and preoperative sagittal vertical axis, with an odds ratio of 1.15 (95% confidence interval, 1.04 to 1.28) per 2-cm increase. Factors associated with lower risk of revision included use of bone morphogenetic protein-2 (BMP-2) (odds ratio, 0.16 [95% confidence interval, 0.05 to 0.47]) and greater diameter rods (odds ratio, 0.51 [95% confidence interval, 0.29 to 0.89]). Body mass index, although initially considered a potential predictor for a revision surgical procedure, was not significantly different between primary and revision cohorts on univariate analysis and was therefore not input into the multivariate model. All patients improved in two-year health-related quality-of-life scores; revision subjects had lower overall improvement (Scoliosis Research Society [SRS] score; p = 0.016) from baseline. Revision status did not predict two-year patient satisfaction (p = 0.726), as measured by the SRS Satisfaction domain (SRS-22r). Conclusions: Patients with greater preoperative sagittal vertical axis and high total body mass are at a higher risk for a revision surgical procedure following procedures to treat adult spinal deformity. Larger diameter rods and BMP-2 were associated with decreased revision odds. Revisions did not impact patient satisfaction at two years. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.